Occupational Hazards and Health Challenges in Bricklaying: An Analysis - Henderson, Laura; Thompson , Samuel (Ayden Journal of Engineering and Applied Sciences, 2024)
In a developing country like Nigeria, construction industries plays an important role and bricklayers are mostly involved in this sector. A significant number of individuals are directly involved in this sector too, and the number is growing at a fast rate in the cities. Due to several occupation health risks, this sector is placed top of the list according to workplace accidents and injuries. Moreover, socioeconomically poor people, particularly from rural areas, are engaged in this sector. Research on occupational health in this occupation is highly needed to give safety and awareness to the bricklaying workers. This work is a review of researches from the available published articles to identify a spectrum of occupational health problems of bricklayers. This profession is associated with a lot of hazards. The research on occupational health hazard of this research may create more awareness to these bricklayers on the risks associated with their professions, and ways to promote safety. Amongst health challenges associated with the profession. The definition of term are dis cuss while the objectives of this article will be discuss under the following sub-heading – identifying different types of hazards among bricklayers, enumerate types of hazards, list the risk factors to hazard among bricklayers and possible harmful effect, mention health challenges associated with bricklaying, identify possible preventive measure. Methodology and review of related articles base on objectives of the paper, observation, discuss of the observations based on different facts retrieved from different author.